Care and outcomes of urban and non-urban out-of-hospital cardiac arrest patients during the HeartRescue Project in Washington state and North Carolina. (July 2020) - Kragholm, Kristian; Hansen, Carolina Malta; Dupre, Matthew E.; Strauss, Benjamin; Tyson, Clark; Monk, Lisa; Pearson, David A.; Nelson, R. Darrell; Fosbøl, Emil L.; Starks, Monique; Jollis, James G.; Shin, Jenny; et al.
Abstract: Aim: We examined overall and temporal differences in out-of-hospital cardiac arrest (OHCA) care and outcomes by urban versus non-urban setting separately for North Carolina (NC) and Washington State (WA) during HeartRescue initiatives and associations of urban/non-urban settings with outcome by state. Methods: OHCAs of presumed cardiac etiology from counties with complete registry enrollment in NC during 2010–2014 (catchment population = 3, 143, 809) and WA during 2011–2014 (catchment population = 3, 653, 506) were identified. Geospatial arrest location data and US Census classification were used to categorize urban areas with ≥50, 000 versus non-urban <50, 000 people. Results: Included were 7731 NC cases (78.9% urban) and 4472 WA cases (85.8% urban). Bystander cardiopulmonary resuscitation (CPR) increased from 36.9% (2010) to 50.3% (2014) in NC non-urban areas versus 58.2% (2011) to 69.2% (2014) in WA; and from 39.3% to 51.1% in NC urban areas versus 52.4% to 61.8% in WA. Crude discharge survival odds ratio (OR) was 2.49 (95%CI 1.96–3.16) for urban versus non-urban NC cases not declared dead in field ( N = 4241). Adjusted for age, sex, public location, bystander-witness status, time between emergency call and emergency medical service (EMS) arrival, calendar-year, bystander and first-responder CPR and defibrillation and direct PCI-center transport, OR was 1.30 (95%CI 0.98–1.73). In WA, corresponding crude and adjusted ORs were 1.38 (95%CI 0.99–1.93) and 1.46 (95%CI 1.00–2.13). In both states, bystander and first-responder CPR and defibrillation and direct PCI-hospital transport were associated with increased survival. Conclusions: During HeartRescue initiatives, bystander CPR increased in urban and non-urban locations. Bystander and first-responder interventions and direct PCI-hospital transport were associated with improved outcomes, including in non-urban areas.